Constructing environment-friendly return road of metals from e-waste: Combination of physical separation technologies. (February 2016) - Ruan, Jujun; Xu, Zhenming
Abstract: Metals are vital raw materials for industrial production and are consuming rapidly as the development of the world. People are always enthusiasm about searching new metal resource even if the results are more and more disappointed. Thus, return of consumed metals is crucial for substantial development of the world. E-waste was rapidly generated together with the innovation of electronic industry. E-waste is called urban mine and metals accounted for above 70 wt%. Recover e-waste is significant for returning metals. However, because of employing crude recovery technology, serious environmental pollution had been generated in the places of recovering e-waste. Environment-friendly and efficient technology has been the pressing demand in the return of metals from e-waste. This paper reported how to construct environment-friendly return road of metals from e-waste. The road was advised to be constructed by physical technologies of crushing, magnetic separation, eddy current separation, corona electrostatic separation, vacuum metallurgy separation and et al. For improving the efficient of the return road, the finished and future works of each technology were presented and proposed. For improving the added value of the recovered metals, further processing was planned in the return road. Additionally, some efforts on environmental friendly construction of the return road were presented. At last, three constructed return roads of metals (above 88 wt% metals were recovered) from e-waste were reported. We expect this paper can contribute to the treatment of e-waste and the development of cyclic economy.